2017
DOI: 10.3892/ol.2017.7415
|View full text |Cite
|
Sign up to set email alerts
|

Chloroquine affects autophagy to achieve an anticancer effect in EC109 esophageal carcinoma cells in�vitro

Abstract: Abstract. Esophageal carcinoma is a malignancy that severely threatens human health, with a high incidence rate and a low 5-year survival rate. Resistance to chemotherapy frequently emerges during its treatment, partly due to the induction of autophagy. Therefore, targeting autophagy may be a promising therapeutic approach for the treatment of esophageal carcinoma. In the present study, it was investigated how chloroquine (CQ) can influence the growth ability and biological behaviors of EC109 esophageal squamo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…Although several clinical trials showed the benefits of chloroquine as an anti-tumor drug ( 308 ), the precise molecular mechanisms of chloroquine-mediated effects has not been established. It was proposed that chloroquine may influence autophagy ( 309 ). Chloroquine in combination with other chemotherapeutic drugs could increase the efficiency of drug treatment, although it can accelerate chemotherapy-associated organ injury ( 301 ).…”
Section: Other Pharmacological Approachesmentioning
confidence: 99%
“…Although several clinical trials showed the benefits of chloroquine as an anti-tumor drug ( 308 ), the precise molecular mechanisms of chloroquine-mediated effects has not been established. It was proposed that chloroquine may influence autophagy ( 309 ). Chloroquine in combination with other chemotherapeutic drugs could increase the efficiency of drug treatment, although it can accelerate chemotherapy-associated organ injury ( 301 ).…”
Section: Other Pharmacological Approachesmentioning
confidence: 99%
“…During the initiation of autophagy, LC3-I is cleaved and lipidated to form LC3-II; p62 is another autophagy marker, which is sequestered within autophagosomes, followed by degradation by lysosomes ( 37 ). Treatment with CQ induces the formation of autophagosomes, with inhibition of autophagosome degradation in the later stage of autophagy ( 38 ). The decrease in HC10-specific forms of B*2704 observed in the presence of CQ may be justified on the basis of the fact that although CQ treatment inhibits autophagy, it can induce ER stress as well as UPR through the PERK-eIF2α-ATF4 pathway ( 39 ), so that the clearance of aggregated forms of the protein may be UPR-driven.…”
Section: Discussionmentioning
confidence: 99%
“…Physiological conditions refer to those conditions which occur in nature for the cellular system and no inner or outer stress is induced. The parameters values were perturbed to capture all the possible qualitative behaviours that the given network can exhibit (e.g., with the addition of ascorbate, the inactivation rate of KRAS was increased; in cases of chloroquine treatment, the inactivation rate of mTOR was induced) and the level of autophagy was decreased [ 49 , 50 ].…”
Section: Methodsmentioning
confidence: 99%